2003
DOI: 10.1038/sj.jp.7210983
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Abnormalities in Severe Neonatal Necrotizing Enterocolitis: 25 Years Later

Abstract: Necrotizing enterocolitis (NEC), the most common surgical emergency in newborns, remains a therapeutic challenge for clinicians. The hematological manifestations associated with NEC were first described 25 years ago. This review discusses current knowledge of the pathophysiology involved in disturbances in megakaryocytopoiesis, coagulation, leukopoiesis, and erythropoiesis that accompany the clinical entity NEC. The discussion includes current understanding of and potential strategies for treating the hematopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 68 publications
1
36
2
1
Order By: Relevance
“…The lower leukocyte counts we found in surgically treated infants as well as in Bell stage III (P ¼ 0.05) are in keeping with previous findings. 3,12,13 However, neither in the present study nor in another study by Voss et al 14 of infants with a mean GA of 31 weeks, were there differences in leukocyte count between survivors and non-survivors. However, in more mature infants with NEC, low leukocyte counts were associated with increased mortality.…”
Section: Discussioncontrasting
confidence: 77%
“…The lower leukocyte counts we found in surgically treated infants as well as in Bell stage III (P ¼ 0.05) are in keeping with previous findings. 3,12,13 However, neither in the present study nor in another study by Voss et al 14 of infants with a mean GA of 31 weeks, were there differences in leukocyte count between survivors and non-survivors. However, in more mature infants with NEC, low leukocyte counts were associated with increased mortality.…”
Section: Discussioncontrasting
confidence: 77%
“…These varieties of neonatal neutropenia are well described. 2,20,[22][23][24][25] However, we found that 43% of the late-onset cases had no recognized underlying cause. Some of these might have been the benign variety of neutropenia sometimes termed, 'idiopathic neutropenia of prematurity'.…”
Section: Discussioncontrasting
confidence: 40%
“…6,18,22 and the associated morbidity due to sepsis. 10,11,23 have been previously reported in populations of more mature neonates. Moreover, the autonomous role of thrombocytopenia in the development of IVH has been also questioned by other studies.…”
Section: Discussionmentioning
confidence: 92%
“…19 Moreover, the efficacy of platelet transfusions in the reduction of the adverse neonatal outcome is still questionable. 10,18 Uncertainness regarding the riskbenefit ratio of platelet transfusions demonstrates the need for studies that will help in the development of appropriate strategies for the management of thrombocytopenia in very preterm born neonates. However, the high risk of bleeding in non-transfused preterm infants and platelet transfusion-associated complications, 19,20 restricts the interventional design for research in this field.…”
mentioning
confidence: 99%